Morphological variation and sexual dimorphism of pteropodid bats in selected sites in Mindanao - Ramos, Neil Carlo (2011)
The morphological variation and sexual dimorphism of Pteropodid bats from selected sites in Mindanao were studied. Eight collected sample species were examined, namely: Rousettus amplexicaudatus, Ptenochirus minor, Eonycteris spelaea, Megaerops wetmorei, and Haplonycteris whiteheadi. Seven morphological characteristics were used as basis for comparison of the different bat species. C. brachyotis, P. jagori, P. mior, R. amplexicaudatus, H. whiteheadi and H. fischerii followed the same pattern, which conformed to what some literature showed. These bats followed a general pattern where the species found in highlands were quite larger than those I the lowlands, in conformity with Bergmann?s Rule. This is apparently due to the effect of altitude, temperature and air density on the required flying effort, temperature regulation of bats, and the effect of ecological factors like resource competition, overpopulation, predator and threat avoidance, which leads to them being smaller. Ear pinna length and hind foot length may be explained by the effect of flight aerodynamics, sound sensitivity of the ear, and several other factors which modifies these bats? morphological characteristics. No significant variation between sexes of a species was discovered most probably due to different biases in dimorphism of bats. The study recommends further study of these variations to provide more concrete data and to be able to come up with appropriate conservative measures based on the implications of these variations